Influenza A virus acquires enhanced pathogenicity and transmissibility after serial passages in swine - Wei, K.; Sun, H.; Sun, Z.; Sun, Y.; Kong, W.; Pu, J.; Ma, G.; Yin, Y.; Yang, H.; Guo, X.; Chang, K.-C.; Liu, J. (American Society for Microbiology, 2014)
Genetic and phylogenetic analyses suggest that the pandemic H1N1/2009 virus was derived from well-established swine influenza lineages; however, there is no convincing evidence that the pandemic virus was generated from a direct precursor in pigs. Furthermore, the evolutionary dynamics of influenza virus in pigs have not been well documented. Here, we subjected a recombinant virus (rH1N1) with the same constellation makeup as the pandemic H1N1/2009 virus to nine serial passages in pigs. The severity of infection sequentially increased with each passage. Deep sequencing of viral quasispecies from the ninth passage found five consensus amino acid mutations: PB1 A469T, PA 1129T, NA N329D, NS1 N205K, and NEP T48N. Mutations in the hemagglutinin (HA) protein, however, differed greatly between the upper and lower respiratory tracts. Three representative viral clones with the five consensus mutations were selected for functional evaluation. Relative to the parental virus, the three viral clones showed enhanced replication and polymerase activity in vitro and enhanced replication, pathogenicity, and transmissibility in pigs, guinea pigs, and ferrets in vivo. Specifically, two mutants of rH1N1 (PB1 A469T and a combination of NS1 N205K and NEP T48N) were identified as determinants of transmissibility in guinea pigs. Crucially, one mutant viral clone with the five consensus mutations, which also carried D187E, K211E, and S289N mutations in its HA, additionally was able to infect ferrets by airborne transmission as effectively as the pandemic virus. Our findings demonstrate that influenza virus can acquire viral characteristics that are similar to those of the pandemic virus after limited serial passages in pigs.